Geochemistry of cryoconite and soils in the Central Caucasus region and its environmental implications - Ivan Kushnov; Evgeny Abakumov; Rustam Tembotov; Vyacheslav Polyakov (Journal of Mountain Science, 2021)

Systematic Validation Study of an Unsteady Cavitating Flow over a Hydrofoil Using Conditional Averaging: LES and PIV - Elizaveta Ivashchenko; Mikhail Hrebtov; Mikhail Timoshevskiy; Konstantin Pervunin; Rustam Mullyadzhanov (Journal of Marine Science and Engineering, 2021)
We present results of Large-eddy simulations (LES) modeling of steady sheet and unsteady cloud cavitation on a two-dimensional hydrofoil which are validated against Particle image velocimetry (PIV) data. The study is performed for the angle of attack of 9° and high Reynolds numbers ReC of the order of 106 providing a strong adverse pressure gradient along the surface. We employ the Schnerr–Sauer and Kunz cavitation models together with the adaptive mesh refinement in critical flow regions where intensive phase transitions occur. Comparison of the LES and visualization results confirms that the flow dynamics is adequately reproduced in the calculations. To correctly match averaged velocity distributions, we propose a new methodology based on conditional averaging of instantaneous velocity fields measured by PIV which only provides information on the liquid phase. This approach leads to an excellent overall agreement between the conditionally averaged fields of the mean velocity and turbulence intensity obtained experimentally and numerically. The benefits of second-order discretization schemes are highlighted as opposed to the lower-order TVD scheme.

Antifungal Properties, Abiotic Stress Resistance, and Biocontrol Ability of Bacillus mojavensis PS17 - Roderic Gilles C. Diabankana; Daniel M. Afordoanyi; Radik I. Safin; Rustam M. Nizamov; Lilia Z. Karimova; Shamil Z. Validov (Current Microbiology, 2021)

Possible role of small secreted peptides (SSPs) in immune signaling in bryophytes - Irina Lyapina; Anna Filippova; Sergey Kovalchuk; Rustam Ziganshin; Anna Mamaeva; Vassili Lazarev; Ivan Latsis; Elena Mikhalchik; Oleg Panasenko; Oleg Ivanov; Vadim Ivanov; Igor Fesenko (Plant Molecular Biology, 2021)

Adaptation to climate change in irrigated agriculture in Uzbekistan* - Shukhrat Mukhamedjanov; Azamat Mukhomedjanov; Rustam Sagdullaev; Nazokat Khasanova (Irrigation and Drainage, 2021)
In recent years, climate change in Central Asia, especially in Uzbekistan, has resulted in sharp alternation of dry and wet years. In such conditions, agriculture has turned into the most vulnerable sector. Agricultural producers have not been able to adapt to such variations of climatic conditions. Traditional irrigation approaches and agronomic operations are becoming unacceptable against the background of severe droughts or heavy rains. Moreover, intra‐annual distribution of precipitation and air temperature has changed. Especially in agriculture, increased rainfall in spring and summer and decreased rainfall in autumn and winter has had a negative impact. In 2013, the Global Water Partnership initiated the Water, Climate, and Development Programme for Caucasus and Central Asia. In the Fergana Valley of Uzbekistan, a project was implemented to study the possibility of agriculture adaptation to climate change within the framework of this programme. This article presents an analysis of long‐term data received from 1960 to 2014 on air temperature and precipitation. As a result of these studies, it has been determined that we can forecast the current year's weather conditions if we find a similar year in recent years. For the Fergana Valley of Uzbekistan, it has been established that we have a stable spring, when winter is cold with heavy precipitation, and we have a cold spring and summer with high precipitation, when we have a warm winter with low precipitation. Past experience has shown that the use of water for irrigation, taking into account climatic conditions, has a significant impact on reducing irrigation water and increasing crop yields.